Treatment of azo dye-containing wastewater by a Fenton-like process in a continuous packed-bed reactor filled with activated carbon - Luís M. Madeira (2012)
In this work, oxidation with a Fenton-like process of a dye solution was carried out in a packed-bed reactor. Activated carbon Norit RX 3 Extra was impregnated with ferrous sulfate and used as catalyst (7 wt.% of iron). The effect of the main operating conditions in the Chicago Sky Blue (CSB) degradation was analyzed. It was found that the increase in temperature leads to a higher removal of the dye and an increased mineralization. However, it also increases the iron leaching, but the values observed were below 0.4 ppm (thus, far below European Union limits). It was possible to reach, at steady-state, a dye conversion of 88%, with a total organic carbon (TOC) removal of ca. 47%, being the reactor operated at 50 ◦C, pH 3, Wcat/Q = 4.1 g min mL−1 (Wcat is the mass of catalyst and Q the total feed flow rate) and a H2O2 feed concentration of 2.25 mM (for a CSB feed concentration of 0.012 mM). The same performance was reached in three consecutive cycles.